2016
DOI: 10.1186/s12934-016-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Putative virulence factors of Corynebacterium pseudotuberculosis FRC41: vaccine potential and protein expression

Abstract: BackgroundCorynebacterium pseudotuberculosis, a facultative intracellular bacterial pathogen, is the etiological agent of caseous lymphadenitis (CLA), an infectious disease that affects sheep and goats and it is responsible for significant economic losses. The disease is characterized mainly by bacteria-induced caseous necrosis in lymphatic glands. New vaccines are needed for reliable control and management of CLA. Thus, the putative virulence factors SpaC, SodC, NanH, and PknG from C. pseudotuberculosis FRC41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
0
27
0
2
Order By: Relevance
“…Currently available diagnostic tools provide limited efficacy. Recent analysis of the C. pseudotuberculosis pangenome allowed the discovery of new bacterial proteins presenting B‐cell epitopes (Santana‐Jorge et al ., ), and another study provided new insights in the use of the CP40 protein as an immunogenic through bioinformatics analysis (Droppa‐Almeida et al ., ). By employing some of these newly discovered antigens in the development of immunoenzymatic assays, the present work demonstrated that several of these molecules are broadly recognized by the host immune system and thus can be used to support accurate immunodiagnostic assays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently available diagnostic tools provide limited efficacy. Recent analysis of the C. pseudotuberculosis pangenome allowed the discovery of new bacterial proteins presenting B‐cell epitopes (Santana‐Jorge et al ., ), and another study provided new insights in the use of the CP40 protein as an immunogenic through bioinformatics analysis (Droppa‐Almeida et al ., ). By employing some of these newly discovered antigens in the development of immunoenzymatic assays, the present work demonstrated that several of these molecules are broadly recognized by the host immune system and thus can be used to support accurate immunodiagnostic assays.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Santana‐Jorge et al . () previously described that this protein has a significant number of B‐cell epitopes. The present in vivo result, which differed from the predictions of the bioinformatics analysis, may result from low expression of the antigen in clinical isolates of the bacteria, or because most bioinformatics software packages base their analyses on murine and human immunological data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete sequencing of the C. pseudotuberculosis genome, combined with the introduction of more advanced technologies, such as mass spectrometry, brought new perspectives to the study of proteins excreted by microorganisms as potential therapeutic, vaccine, or immunoassay targets (D'Afonseca et al 2010;Bastos et al 2012;Araújo et al 2019). Some of the highlighted immunoassay and vaccine development target proteins include diptheric toxin repressor homologue (DTxR), Trx and TrxR thioredoxin complex proteins, LexA proteins, superoxide dismutase-C (SodC), SpaC, neuraminidase H (NanH), and PknG serine/threonine kinases (Trost et al 2010;Hall et al 2011;Lin et al 2016;Santana-Jorge et al 2016).…”
Section: Introductionmentioning
confidence: 99%